Enhancing production and flow of freshwater ecosystem services in a managed Himalayan river system under uncertain future climate - Momblanch, Andrea; Beevers, Lindsay; Srinivasalu, Pradeep; Kulkarni, Anil; Holman, Ian P. (Springer, 2020)
Future climate change will likely impact the multiple freshwater Ecosystem Services (fES) provided by catchments through their landscapes and river systems. However, there is high spatio-temporal uncertainty on those impacts linked to climate change uncertainty and the natural and anthropogenic interdependencies of water management systems. This study identifies current and future spatial patterns of fES production in a highly managed water resource system in northern India to inform the design and assessment of plausible adaptation measures to enhance fES production in the catchment under uncertain climate change. A water resource systems modelling approach is used to evaluate fES across the full range of plausible future scenarios, to identify the (worst-case) climate change scenarios triggering the greatest impacts and assess the capacity of adaptation to enhance fES. Results indicate that the current and future states of the fES depend on the spatial patterns of climate change and the impacts of infrastructure management on river flows. Natural zones deliver more regulating and cultural services than anthropized areas, although they are more climate sensitive. The implementation of a plausible adaptation strategy only manages to slightly enhance fES in the system with respect to no-adaptation. These results demonstrate that water resource systems models are powerful tools to capture complex system dependencies and inform the design of robust catchment management measures. They also highlight that mitigation and more ambitious adaptation strategies are needed to offset climate change impacts in highly climate sensitive catchments
Keywords: adaptation; spatial dependencies; WEAP; water resource systems modelling; catchment management; Climate change